Cinematherapy Meningkatkan Kendali Diri Mahasiswa - Solihatun Solihatun; Evi Fitriyanti; Melina Lestari (Psychocentrum Review, 2020)
The purpose of this study was to determine the effectiveness of cinematherapy in improving student self-control. This research uses a descriptive method with a quantitative approach. The sample of this study were 21 Unindra students. The self control instrument used is a Likert scale model. The results showed the percentage of Pre Test and post test showed that there were 4 students who had self-control in the excellent category of 19%. Furthermore, there are 17 students who have a good category by 81%. Next, if seen from the t test results show that the value of the Pre Test obtained an average of self-control or a mean of 218.9. While the Post Full Self Test value was 222.9. So with that it means descriptively there is a difference in the average of self control between the Pre Test and the Post Test results. However, it is not significant. Based on the value of the correlation coefficient (correlation) of 0.350 with a significance value (sig.) Of 0,000 because the value of Sig. 0,000 <probability 0.05, it can be said that there is a relationship between the Pre Test variable and the Post Test variable. However, it is not significant. So it can be concluded that there is no significant difference in average between Pre-Test and Post-Test self-control, which means that cinematherapy has proven ineffective in increasing the self-control of UNINDRA students.